Wuthering Heights - Sebag-Montefiore, Mary; Marks, Alan (London : Usborne Publishing Ltd, 2010)
Suitable for children whose reading ability and confidence allows them to tackle longer and complex stories, this title tells the doomed love story of Cathy and Heathcliffe as seen through the eyes of a neighbor, Mr Lockwood, and the old nurse, Nelly Dean
Keywords: Children's stories; Manners and customs -- fiction